Komunitas Burung pada Pegunungan Bawah dan Sub-Pegunungan Di Taman Nasional Gunung Halimun Salak - Kanthi Hardina; Yeni Aryati Mulyani; Ani Mardiastuti (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
Bird diversity has been known to be affected by various factors, including elevational gradient. The objective of this study was to describe the bird community trend and its associated habitat conditions on lower mountain and sub-mountain areas. The study was conducted in September-October 2017 in Gunung Halimun Salak National Park, West Java, Indonesia. Bird data were collected using point count method. Data were analyzed by using Shannon-Wiener (H’) diversity index, Margalef’s richness index (DMg), and Bray-Curtis similarity index. Birds were grouped into guilds according to their major diet. There were 54 bird species (23 families) in both altitudes, of which 23 species were found in the lower altitude and 33 species were found in the higher altitude. Contrary to most studies elsewhere, the diversity and richness indices were significantly higher at the sub mountain (H’=2.85; DMg=5.96) than at lower mountain (H'=2.38; DMg=3.79). Insectivores were dominant in both altitudes, although similarity index was low (5%). Bird diversity was higher in the higher altitude due to habitat condition. Lower montain had a higher anthropogenic disturbance than the sub-mountain.